Crosslinking of progesterone receptor to DNA using tuneable nanosecond, picosecond and femtosecond UV laser pulses. - Russmann, C (1997)
UV laser crosslinking is a potentially powerful tool to investigate transient DNA-protein interactions and binding kinetics in intact cells. As the processes underlying UV laser crosslinking are not fully understood, we have performed a study of the influence of laser pulses with different physical parameters on crosslinking of the progesterone receptor to an oligonucleotide containing a hormone-responsive element. We also studied the influence of the various parameters on the amount of laser-irradiated DNA that can be correctly primer extended as an operational measurement of DNA integrity. A strong influence of pulse intensity and pulse length on the crosslink yield was found, likely due to a change in the 'two photon' processes responsible for crosslinking. The highest efficiency of protein crosslinking to DNA was achieved with femtosecond pulses and should be sufficient to enable use of this technique for in vivo studies.